The online purchase intention among graduates / Mohamad Faizul Mohamad Zali and Aidi Shahrizad Kusim - Mohamad Zali, Mohamad Faizul; Kusim, Aidi Shahrizad (Faculty of Business and Management, 2013)
The research was providing information about the online purchase intention among graduates. As we know that in recent years, online shopping has become more popular but not of the people like to online shopping. Some reasons people did not like to doing online shopping because online trust, previous experience and also branding itself. The objective of this research is to determine the level of customer’s awareness toward online purchase intention. Second is to examine the relationship between branding with online purchase intention among graduates. Third is to investigate the relationship between online trusts towards online purchase intention. Forth is to research the prior online purchase experience has any relationship to online purchase intention. Fifth objective is to determine from three independent variables which most important to the online purchase intention. All the data collection will be analyzed using Statistical Package for Social Science (SPSS). In General, the results of this study shows that online trust is most important toward online purchase intention. Method of collection data are primary and secondary data such as questionnaire, interview, text books, and journals and so on. Researcher used questionnaire as a main instrumental in data collection method and involve 100 respondents among graduates. The conclusion for this study is from the outcome of finding and analysis. Recommendations for future research have been discussed in the final chapters.